More for Less – If Only We Could Get Them to Do It! - Robert J. Sokol (HealthcarePapers, 2013)
Systems for the provision of healthcare need to be improved, since costs are already high and rising along with the needs of an aging population. In considering evaluations of two programs from opposite ends of the country, inferences can differ depending on the observer. While the demographic-healthcare time bomb we're faced with should have been obvious years ago, the need for positive action is upon us. The difficult issues are not so much errors in the past as they are (1) disingenuous suggestions that this isn't a cost problem, (2) a need to improve team behaviors and functions to increase the value of the care provided (i.e., quality for expenditure), (3) a lack of engagement and enthusiasm by providers for new systems and (4) most importantly, resistance to change brought from outside the care environment and the source and beneficiaries of the change not being primarily the local stakeholders. Care providers and recipients, as well as the governments funding healthcare will need to be convinced that we are successfully increasing healthcare value and improving patient outcomes.
Keywords: Health Human Resource, Population Health, Needs-based Planning, Care Delivery Programs